The Proselytization Aspect in the Novel Suriati Based on the Proselytization Approach of the Malay Methodology Theory - Ishak, Nadia; Kamarudin, Kamariah (Malay Literature, 2019)
The writing of religious novels is one of the most effective mediums of proselytization that can be used by writers to spread the teachings of Islam and increase people's faith in Allah SWT. This study uncovers the aspects of proselytization in novels that employ religious themes as backgrounds for works dealing with family conflict. The focus is on Azizi Haji Abdullah' novel, Suriati, which shows the strength and effectiveness of proselytization in leading people towards a life of goodness and avoidance of falsehood. The proselytization approach of the Malay Methodology (Pengkaedahan Melayu) was employed as a framework for analysis. The findings of this study reveal that proselytizing elements are able to create an interest in Islam and may be used as a means to spread the word of Islam. Keywords: proselytization, religion, theory, faith, society